To the 110 anniversary since the birth of professor E.A.Vasyukova - Alexandr Sergeevich Ametov (Endocrinology Research Centre, 2015)
110 years ago was born famous scientist, talented teacher and doctor, organizer of public health, honoured worker of science of RSFSR, doctor of medicine, professor Ekaterina Alekseevna Vasyukova. Ekaterina Alekseevna had long and difficult career path - from research assistant to the director of the All-Russian Institute of Experimental Endocrinology(now Endocrinology Research Centre), was head of it for 10 years, a long time was head of the Department of Endocrinology at the Central Institute of Advanced Medical Ministry of Health (now the Academy of Postgraduate Education). She had more than 200 publications, including 14 monographs, collections and algorithms in endocrinology. Under her leadershipthere were defended 16 doctoral and 63 master's theses. The main areas of her research were the methods of diagnostics and treatment of diabetes, Cushing's disease, thyroid diseases, abnormalities of reproductive growth. In 1971 she had identified the current trends in the nativeclinical endocrinology, which were the relationship between the central nervous system and the endocrine glands; immunopathology in endocrinology; study of the prevalence and prevention of diabetes. EkaterinaAlekseevnawassensitive person, a great clinician, a professional teacher. She had great authority and respect among the medical community of our country and abroad.